Contemporary security and strategy - Snyder, Craig A., 1965-; Snyder, Craig A. (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2012)
"This text brings together a range of specially-commissioned chapters to provide an accessible introduction to Security Studies in the 21st century. The third edition has been expanded to cover non-military challenges to security, and includes new learning aids"--
Machine generated contents note: -- Contemporary Security and Strategy -- Realism and Security Studies -- Beyond Strategy: Critical Thinking on the New Security Studies -- Environmental Security -- Human Security -- Security Implications of the Arms Trade -- The Causes of War -- Military Strategy and the New World Order -- The Transformation of War -- Nuclear Strategy -- Challenges and Opportunities for the Nuclear Non-Proliferation Regime -- Terrorism and Insurgency -- Intervention: The Utility of Force in International Politics -- Great Powers and the International System: Between Unilateralism and Multilateralism -- Regional Security and Regional Conflict.
Includes bibliographical references (p. 330-355) and index.
Keywords: National security; Security, International; Strategy; POLITICAL SCIENCE / Political Freedom & Security / International Security; POLITICAL SCIENCE / Peace; POLITICAL SCIENCE / International Relations / General